Molecular Mechanisms of Injury in HIV-Associated Nephropathy - Rednor, Samuel J.; Ross, Michael J. (Frontiers in Medicine, 2018)
HIV-associated nephropathy (HIVAN) is an important cause of secondary focal glomerulosclerosis that occurs primarily in persons of African ancestry with advanced HIV disease. Although HIVAN is characterized by severe proteinuria and rapid progression to end stage renal disease without treatment, the phenotype is markedly attenuated by treatment with antiretroviral medications. HIV infection of glomerular and tubular epithelial cells and subsequent viral gene expression is a key contributor to HIVAN pathogenesis and the kidney can serve as reservoir for HIV strains that differ those in blood. HIV gene expression in renal epithelial cells leads to dysregulation of cellular pathways including cell cycle, inflammation, cell death, and cytoskeletal homeostasis. Polymorphisms in the APOL1 gene explain the marked predilection of HIVAN to occur in persons of African descent and HIVAN. Since HIVAN has the strongest association with APOL1 genotype of any of the APOL1-associated nephropathies, studies to determine the mechanisms by which HIV and APOL1 risk variants together promote kidney injury hold great promise to improve our understanding of the pathogenesis of APOL1-mediated kidney diseases.